2018
DOI: 10.1017/s002966511800006x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to address household food insecurity in high-income countries

Abstract: Household food insecurity is a serious public health concern in high-income countries. Canada and the USA regularly monitor household food insecurity, while in other countries, such as the UK, it has been the rapid rise of food bank usage that has drawn increased attention to this longstanding, but largely overlooked, problem. This review evaluates evidence on interventions intended to reduce household food insecurity in high-income countries. Research on social protection interventions suggests both cash tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
134
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 118 publications
2
134
0
4
Order By: Relevance
“…In order to address food insecurity, national nutrition policy and welfare policy must take these inequalities into account and focus on increasing reliable access to nutritional food, such as through the provision of food vouchers additional to welfare payments and subsidised groceries. Moreover, there is a need to address the underlying structural drivers of entrenched disadvantage and deficiencies in social protection which result in government income support payments below poverty line levels [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In order to address food insecurity, national nutrition policy and welfare policy must take these inequalities into account and focus on increasing reliable access to nutritional food, such as through the provision of food vouchers additional to welfare payments and subsidised groceries. Moreover, there is a need to address the underlying structural drivers of entrenched disadvantage and deficiencies in social protection which result in government income support payments below poverty line levels [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In a US-based qualitative study with low-income residents, participants reported that increasing the number of farmers' markets and community gardens would improve access to healthful foods [4], suggesting that these may be promising approaches for future research. But ultimately major upstream changes to the welfare system are needed as foodbanks only address one issue that food-insecure populations experience [37].…”
mentioning
confidence: 99%
“…Monitoring would be national and regular and targets for reduction would be articulated and reported on. Without this, social enterprise food security strategies will likely be limited to local effects only, similar to community kitchens and gardens (Loopstra, ).…”
Section: Discussionmentioning
confidence: 99%
“…These well‐known ‘pillars’ of food security, informed by the human right to food and articulated by United Nation's agencies (The Food & Agriculture Organization of the United Nations, ), can be used to monitor the prevalence and drivers of food insecurity and design programme and policy responses. The evidence documenting the growth, and yet limitations in the capacity of food banks to fulfil the right to food, and on the over‐reliance of Western governments on this charitable system, is substantial (Bazerghi, McKay, & Dunn, ; Loopstra, ). Social enterprises are a newer evolution in civil society responses to food insecurity, and merit evaluation and consideration for their contributions and limitations.…”
Section: Introductionmentioning
confidence: 99%